Transgenerational remembrance : performance and the Asia-Pacific war in contemporary Japan - Nakamura, Jessica (Performance works., 2020)
"Transgenerational Remembrance examines the legacy of the Asia-Pacific War in Japan (1931-1945) through contemporary output in theater and performance art. This book explicates art and theatrical productions dealing with kamikaze pilots, Japanese imperialism, comfort women, the Battle of Okinawa, and Japanese American internment"--